STRATEGI MANAJEMEN KURIKULUM DALAM RANGKA PELAYANAN PEMBELAJARAN DAN PENINGKATAN KOMPETENSI PESERTA DIDIK DI SMP NEGRI 04 CIKARANG BARAT - Muhammad Sulthon Syahidillah; Muhamad Taufik Bintang Kejora; Yadi Fahmi Arifudin (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze curriculum management practices at SMP Negeri 04 Cikarang Barat, focusing on curriculum planning, organizing, implementation, as well as monitoring and evaluation in supporting educational quality improvement. Methods: This study employed a descriptive qualitative approach. Research participants consisted of the vice principal for curriculum affairs, teachers, and other school stakeholders involved in curriculum management. Data were collected through observations, in-depth interviews, and documentation studies involving curriculum documents, learning schedules, and supporting administrative records. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. Results: The findings revealed that curriculum management at SMP Negeri 04 Cikarang Barat has been implemented systematically and collaboratively. Curriculum planning was conducted through the preparation of KOSP involving various stakeholders. Curriculum organization was based on teacher workload, Dapodik data, and MGMP recommendations. Learning implementation applied diverse instructional methods aligned with student characteristics. Novelty: The novelty of this study lies in its comprehensive analysis of curriculum management in a junior high school implementing both the 2013 Curriculum and the Merdeka Curriculum simultaneously while facing limitations in human resources and educational facilities.